2000
DOI: 10.1152/ajpheart.2000.279.5.h2326
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes in apolipoprotein E-knockout mice

Abstract: Apolipoprotein E-knockout (ApoE-KO) mice develop advanced atherosclerotic lesions by 1 yr of age and have been well characterized pathologically and morphologically, but little is known regarding their cardiovascular physiology and hemodynamics. We used noninvasive Doppler ultrasound to measure aortic and mitral blood velocity and aortic pulse-wave velocity in 13-mo-old ApoE-KO and wild-type (WT) mice anesthetized with isoflurane. In other mice from the same colony, we measured systolic blood pressure, body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 31 publications
14
116
4
Order By: Relevance
“…Although the atherosclerotic lesions are progressive and may become severe, their functional effect on blood flow and physiology is largely unknown. Cardiovascular reserve relevant to exercise performance is reduced (Niebauer et al, 1999), and we have previously shown a 55% increase in aortic and mitral flow velocities and a 59% increase in heart-weight to body-weight ratio at 1 year of age (Hartley et al, 2000) consistent with volume overload hypertrophy. However, the effect and significance of systemic and coronary arterial lesions and of the cardiac hypertrophy on coronary blood flow and coronary flow reserve in ApoE −/− mice is unknown.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the atherosclerotic lesions are progressive and may become severe, their functional effect on blood flow and physiology is largely unknown. Cardiovascular reserve relevant to exercise performance is reduced (Niebauer et al, 1999), and we have previously shown a 55% increase in aortic and mitral flow velocities and a 59% increase in heart-weight to body-weight ratio at 1 year of age (Hartley et al, 2000) consistent with volume overload hypertrophy. However, the effect and significance of systemic and coronary arterial lesions and of the cardiac hypertrophy on coronary blood flow and coronary flow reserve in ApoE −/− mice is unknown.…”
Section: Introductionmentioning
confidence: 54%
“…Our findings in mice are in substantial agreement with the findings in rats and in man that age and baseline velocity are the major factors determining H/B in the absence of coronary stenoses. Conditions which increase baseline cardiac work such as pressure (Rockman et al, 1993) or volume (Hartley et al, 2000) overload would be expected to decrease coronary reserve in mice as they do in man (Marcus et al, 1982). However, it remains unclear whether the lower baseline velocity in Old versus Young mice is due to reduced demand at rest or to differential sensitivity to isoflurane.…”
Section: H/b In Mice Versus Manmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of consideration is particularly important when interpreting traits of apoE-/-mice that are quantitative and not directly explainable by the function of apoE in lipid metabolism. These include blood pressure (9), kidney damage (10), behavior (11), and susceptibility to infections (12,13). The observed phenotypes could be secondary to hyperlipidemia and/or atherosclerosis induced by lack of apoE, or the consequence of yet-to-be defined functions of apoE.…”
mentioning
confidence: 99%
“…Doppler and 2D mModeguided echocardiography studies were performed on isofluraneanesthetized mice as described (15,16).…”
Section: Preparation Of Ianphdmentioning
confidence: 99%